Isolation of Antibiotic-Producing Microorganisms from Camponotus melanus in the Mangrove Ecosystem against Pathogenic Bacteria - Three Yulinda; Irwan Effendi; Zulkifli Zulkifli; Nursyirwani Nursyirwani; Ummi Mardhiah Batubara (Science, Technology, and Education Care, 2026)
Microorganisms that live in extreme conditions in mangrove ecosystems have unique defence mechanisms that enable them to produce secondary metabolites that function as antibiotics. One of them is the wood ant (Camponotus melanus), which is commonly found in mangrove ecosystems and plays a significant role in these ecosystems. This study aims to identify bacteria associated with C. melanus based on morphological characteristics and biochemical tests, and to test their antibacterial activity against pathogenic bacteria (Aeromonas hydrophila, Pseudomonas aeruginosa, and Staphylococcus aureus). This study was conducted from September to November 2025. The method used was a survey method. The research was conducted from September to November 2025. C. melanus samples were taken from the Marine Station mangrove forest, Dumai City, Riau Province, and analyzed at the Marine Microbiology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The isolation and identification results yielded three bacterial isolates: C1 and C2, suspected to be Bacillus sp., and C3, suspected to be Citrobacter sp. The antibacterial activity test results of the three isolates produced inhibition zones. This indicates that the three isolates have the potential to serve as sources of promising antibiotic compounds for further development